Creating communities of professionalism: addressing cultural and structural barriers. Issue 2 (13th April 2015) - Murphy, Joseph
Abstract : Purpose: – The goal of this narrative synthesis is twofold. The purpose of this paper is to understand the barriers and constraints that hinder or prevent the growth of professional community. The author also want to form an empirical understanding of how educators can be successful in meeting these challenges. In both cases, the author wish to grow this knowledge in the complexity of schooling and the rapids of continuous school improvement. The conceptual architecture for the review is a mixture of research on change and implementation, school improvement, and community. Design/methodology/approach: – The paper can best be described as an integrative review or a narrative synthesis – an interpretation of the literature (Vescio et al., 2008), a method that is especially useful when combing qualitative and quantitative research findings. The author follow guidance from Hallinger in explaining the construction of the paper. The goal is to explore the broadest landscape possible to distill knowledge and understanding on the one hand and provide usable material on the other. In the words of Battistich, the aim is "to develop integrative explanatory concepts that provide people with a useful framework for considering action under particular circumstances." Findings: – The paper concludes that there are dynamic cultural and well-entrenched structural barriers that make the realization of professional community problematic. Some of these elements are visible. Many others are deeply buried in the meta-narrative of school improvement. The author also finds that absent direct attention to these conditions, efforts to nurture professional community in schools will be seriously handicapped. Research limitations/implications: – Narrative syntheses offer the hope of deep understanding of domains of school improvement. They permit the inclusion of findings garnered from an array of methodologies. At the same time, this mode of investigation lacks the precision associated with more structured methods of knowledge accumulation. Even when done well, it places considerable responsibility on investigators in making sense of findings. Originality/value: – By examining research from a wide area of domains, the author is able to construct a comprehensive map of the world of bringing professional community to life in schools for researches, policy actors, developers, and practitioners.